HAKIKAT PENDIDIKAN KELUARGA (PERSPEKTIF AL-QUR’AN DAN HADITS) - Nur Faidah; Ahmad Zumaro (Widya Balina, 2025)
This paper aims to present the essence of family education according to the Qur'an and hadith. To compile this paper, a literature study method was used with the main references being Taisiru al-Aliyyul Qadir li Ikhtishari Tafsir Ibn Kathir, Tafsir Al-Misbah, and Tafsîr al-Qurân al-Hakîm. In addition, it is supplemented with several hadiths. The findings from this discussion indicate that family education is an effort made by parents to develop children's potential, both in intellectual, emotional, spiritual, and skill aspects. Family education aims to ensure the well-being of oneself and those under one's responsibility, as well as to shape the character of independent and mature children. Responsibility for family education is a shared obligation between fathers and mothers. The family plays a very important role in children's education, both consciously and unconsciously. Overall, family education is a learning process that involves all the main members who are part of the family, namely parents (father and mother) and children.